The Effect of Heparin on Bone Metabolism and Orthodontic Tooth Movement in Rats - Behzad Salari; Reza Moradian; Yasaman Kheirandish; Mojgan Alaeddini; Shahroo Etemad‐Moghadam; Shahla Maghsoudi; Ahmad Reza Dehpour (Clinical and Experimental Dental Research)
ABSTRACT Objectives Various attempts have been made to increase the rate of orthodontic tooth movement (OTM). The aim of this study was to determine the effect of different doses of heparin on OTM and paraclinical factors related to bone metabolism in rats. Methods and Materials A total of 24 Sprague‐Dawley rats were randomly divided into three groups of 8 animals each and injected with 0 (control), 3000, and 6000 U/Kg/d heparin sulfate for 4 weeks. Radiographs were obtained at the initiation and at the end of the study period. Orthodontic forces were applied on Day 14 and continued for the next 2 weeks, after which, OTM, optical density, parathyroid hormone (PTH) level, and histologic variables were assessed for each rat. The latter was performed on hematoxylin/eosin–stained sections of the mesial roots of the first molar and included calculation of the osteoclast number, and resorption lacunae depth and number. One‐way analysis of variance, the Tukey test, and a paired‐t‐test were used for statistical analysis (p < 0.05). Results A significant increase in OTM, the number of resorptive lacunae, and PTH secretion was observed in the group that received 6000 U/Kg/d compared with both the other groups. There was no significant difference in optical density, and, therefore, bone density, among the study groups (p > 0.05). Conclusion Heparin injection affects bone metabolism in rats, as shown by the increases in OTM and PTH and its impact on histologic parameters. These effects seem to be dose‐dependent and may be a factor that should be taken into consideration during orthodontic treatment planning.